Mastering video production: techniques, tools, and the creative process / Suzana Baharudin and Syamsulhairi Yaakop - Baharudin, Suzana; Yaakop, Syamsulhairi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In today's fast-paced multimedia landscape, video production has become an essential tool for disseminating information, captivating audiences, and conveying impactful messages across a variety of platforms. Among all media formats, video content stands out due to its ability to integrate both visual and auditory elements, effectively grabbing and maintaining viewer attention more efficiently than many other mediums. This paper examines the fundamental methods of video production, including video capture techniques, hardware selection, and the complexities of editing using industry-standard software like Adobe Premiere Pro. Producing high-quality video requires a careful combination of creativity and technical skill, with each phase of production playing a crucial role in determining the effectiveness and overall quality of the final output.